Effects of several production methods on technological, textural and sensorial properties of emmer (Triticum turgidum ssp. dicoccum) bulgur - Yilmaz, Volkan Arif (J Food Sci Technol, 2020)
In recent years, the interest in primitive wheat species including emmer (Triticum turgidum ssp. dicoccum) wheat and their characteristics have increased due to natural food trends. Bulgur is a nutritious and healthy product with long shelf life, produced from hard wheat species without the need for any additives. The basis of this study was to reveal the potential for bulgur production by the six production methods, combinations of three cooking (traditional, autoclave, microwave) and two drying (hot-air, microwave) methods of emmer wheat. In addition to some physical, chemical and technological properties of emmer wheat, yield, color, cooking time and textural and sensorial properties of the bulgur samples were investigated and statistically significant differences (p < 0.05) were recorded among the bulgur samples. Autoclave cooking had a negative effect on color and got the lowest sensorial acceptability scores. Microwave drying increased fine bulgur formation and shortened the cooking time. The volume and weight increase indexes were increased more than hot-air drying thanks to physical effects of microwave drying on the structure. According to the texture analysis results, microwave cooking increased the adhesivity, and microwave drying increased hardness and springiness. In conclusion, emmer wheat have great potential for bulgur production, and traditional cooked + hot air dried samples had better bulgur properties in overall.